FAKTOR RISIKO GIZI LEBIH PADA ANAK UMUR 9-11 TAHUN DI SEKOLAH DASAR MARSUDIRINI SEMARANG TAHUN 2016 - Herliana Endang Supriyatini; Siti Fatimah Pradigdo; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Overweight is a situation when the body undergoes of excess weight because of due toexceeding energy intake that is stored in the form of reserve fat. Based on the Basic health research 2013, nationally more nutritional problems in children aged 5-12 years is as high as 18.8%. Overweight children tend to continue into adulthood if not solved early. The aim of this research is knowing the risk factors of overweight children aged 9-11 in Marsudirini elementary school Semarang in 2016. This is an explanatory research by case control study design. The sample are students of Marsudirini elementary school Semarang aged 9-11, 32 children, for each consists of 16 cases and 16 controls which chosen by purposive sampling. The analysis was done through chi square. The results showed that the proportion of consumption in the category fast food more often in groups of 56,3% while 31,3% of the normal group (pvalue = 0,285, OR = 2,829), proporsi energy sufficiency level in more categories on the nutritional groups over 75% where as in normal group 18,8%, (pvalue = 0,004, OR = 13,00), the proportion of fat sufficiency level in the category of over 62,5% and 43,8% in the normal grou (pvalue = 0,479, OR = 2,143). Need to do outreach to students of elementary Marsudirini about nutrition problems, especially regarding nutrition is more related to consumption of high energy. It is expected that schools provide counseling about the risk factors associated with more and give nutrition information through the subject matter to the students about the foods that are healthy and nutritious.